"Giving the gift of life twice": Understanding the lived experiences of parent donors and nondonors in pediatric haploidentical hematopoietic cell transplantation. Issue 2 (6th December 2021) - Schaefer, Megan R.; Aguilera, Vanessa; Parris, Kendra; Long, Alanna; Triplett, Brandon; Phipps, Sean
Abstract: Background: The use of parental donors in pediatric haploidentical hematopoietic cell transplantation is increasing, but research on the psychosocial impact of parental donation is currently limited. Objectives: As part of a larger study, we conducted a retrospective, qualitative analysis to explore parental perceptions of the donation process and the impact of being a donor (or nondonor) on parents' adjustment and coping with their child's transplant experience. Methods: Parents/caregivers of children who underwent transplantation with a parental donor or a matched unrelated donor ( N = 136) participated in interviews and completed an open‐ended questionnaire. Results: Six themes were identified in the data: level of understanding and satisfaction; perception of choice; preparation for donation; perceptions of donation and infusion; benefit finding; and psychological impact of transplantation. Most parents were satisfied with the information they received and reported a good understanding of transplantation and donation procedures. Parents were divided on perspectives of choice, but their responses reflect that the necessity of saving their child's life does not allow for choice. They described considerable effort to prepare for transplantation, physically, emotionally, and logistically. Parents acknowledged the psychological impact while identifying positive outcomes that resulted from their child's transplant journey. Conclusions: Results highlight the unique experiences of parental donors and nondonors from the anticipation phase to the completion of their child's transplant. Additionally, findings inform supportive care guidance by highlighting the need to assess parental donors' emotional functioning, provide support post donation, and conduct bereavement follow‐up.